Identifying factors affecting data delivery performance in mobile ad-hoe network routing using a systematic approach - Mohamed, Hazura (2008)
A mobile ad hoc network (MANET) is a collection of mobile nodes dynami- cally forming temporary network without the use of any existing network infrastructure or centralized administration. Due to the mobility of the nodes, as well as the con- tinual arrival and departure of nodes, the topology of the network changes constantly. To manage the data transmission, routing protocols are needed. Therefore, analyzing performance of the protocols becomes crucial to finding an efficient routing protocol. Many performance evaluation of routing protocols have done through trial-and-error simulation experiment. This paper shows a systematic procedure of using Taguchi parameter design in analyzing Destination Sequence Distance Vector (DSDV) routing protocol performance. The affect of terrain size, node speed, network size and pause time on the performance of DSDV routing protocol is identified. Performance is evalu- ated with respect to packet delivery ratio. Based on the simulation data, it was found that the network size and the terrain have significant impact on the performance.